Periodic nanostructures induced by point defects in Pb1-xSnxTe - Saliy, Ya.; Nykyruy, L.; Cempura, G.; Soroka, O.; Parashchuk, T.; Horichok, I. (Physics and Chemistry of Solid State, 2023)
Lead tin telluride solid solutions are excellent candidates for the p-type conduction legs of the thermoelectric generator modules. The investigation of their microstructure properties is an important issue, that can effectively modify their electronic and thermal transport properties. In this work, we show the experimental dependences of the Pb1-xSnxTe component distribution, which were identified as periodic nanostructures with an amplitude of λ ≈ 50-500 nm. The observed periodicity is explained by the generation and recombination of point defects due to diffusion processes during the synthesis, sintering, and annealing of samples. A model describing the formation of such inhomogeneities in Pb1-xSnxTe ternary alloys during isothermal annealing is proposed.